Oxidative gold catalysis meets photochemistry - synthesis of benzo(a)fluorenones from diynes - Nösel, Pascal; Hendrich, Christoph; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Advanced synthesis & catalysis, 2014)
Diynes bearing one terminal and one triarylmethyl-substituted alkyne were converted into complex benzofluorenone derivatives via a one-pot process involving a gold-catalyzed step followed by a photocyclization/oxidation. In the first step an N-oxide was used to position-selectively generate an α-oxo carbenoid at the terminal alkyne which after a regioselective 1,6-carbene transfer along the tethered tritylalkyne and a subsequent aryl 1,2-shift furnished tetraphenylethylene-like derivatives. These intermediates were successfully transformed to fluorenones via oxidative photocyclization.
Im Titel ist der Buchstabe "a" in eckigen Klammern
Gesehen am 29.10.2020